AN EXPERIMENTAL INVESTIGATION OF ANIMATED VIDEO BASED VISUAL LEARNING IN SPORTS EDUCATION - Chhatiye, Sourabh; kaur, Harmanpreet; Turukmane, Pradeep; Sagre, Siddharth; Ahlawat, Ravinder Pal; Nanda, Rupika (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The purpose of this study was to examine the effect of animated video-based visual learning on student athletes enrolled in sport education programs. A pre-test and post-test control group experimental design was utilized for this study. Eighty (80) student-athletes (ages 18-24) enrolled in B. P. Ed. programs were selected for participation and were equally divided between an experimental (n = 40) and control Groups (n = 40). Sports education was measured by a 30-items Exercise Physiology Questionnaire, developed previously with CVR ranging from 0.62 to 1.00. The experimental group received an intervention consisting of eight (8) weeks of animated video-based visual learning with structured lessons covering the important information about Exercise Physiology while the control group did not receive any such intervention. To determine differences in pre and post-test scores within each group, dependent t-tests were conducted, and independent t-tests were conducted to compare post-test scores between the two groups. Statistically significant improvement in sports education was shown among student-athletes who received animated video-based visual learning as compared to those who did not (p <.01). Statistically significant differences were also shown between groups in student-athletes, in that the experimental group outperformed the control group. Results from this study indicate that animated videos are an effective way to increase conceptual understanding in sports education through visual learning.